Sustainable Bank Performance Antecedents in the Covid-19 Pandemic Era: A Conceptual Model - Steph Subanidja; Fangky Antoneus Sorongan; Mercurius Broto Legowo (Ital Publication, 2022)
The study proposes a conceptual model of sustainable bank performance antecedents in the Covid-19 Pandemic Era. This study uses a qualitative perspective. Data gathering is done using depth interviews with the Indonesian Central Bank, the Authority of Financial Services, and the National Commercial Banks Association members. Using ethnography analysis from interviews, focus group discussions, and previous studies shows that many variables affect the performance. However, the exogenous variable on performance is without precisely placing fintech and regulations as an antecedent. The study results then constructed the fintech and regulations as intervening and moderating variables for the performance, whereas the other variables were as business driver variables. The study's improvement is that fintech and regulations are the main antecedents for the performance during the pandemic. Fintech is not only an entity outside the bank but also an innovation inside the bank. Moreover, the other improvement is that the bank is not only an institution of customer trust but also an institution with a full touch of technology. Consequently, banks must adopt fintech, and cooperating with fintech entities is a wise choice. The study then proposes a conceptual model of sustainable bank performance that connects business drivers, fintech, and regulations. Doi: 10.28991/ESJ-2022-06-04-09 Full Text: PDF